LITERASI AKUNTANSI BADAN USAHA MILIK DESA PADA BUMDES SILATRI INDAH WONOSOBO - Widaryanti - Widaryanti; Luhgiatno - Luhgiatno; Rudika - Harminingtyas (Universitas YPPI Rembang, 2023)
AbstractBUMDES Silatri is one of the villages where BUMDes was established. BUMDes Silatri Indah as a partner does not prepare financial reports properly and is not in accordance with applicable accounting standards. Accounts are kept whenever a transaction occurs, regardless of accounting principle, and are limited to recording cash received and paid. This is because BUMDes treasurers do not have accounting education, and BUMDes managers have never received training on financial reporting, thus adding to the complexity of the problems faced by partners. The purpose of this event is to provide knowledge and understanding to prepare financial reports, therefore, through organizing seminars and training. The method of implementing PKM activities is educative. The educational approach discussed is providing knowledge and understanding of BUMDes Silatri Indah management which is reflected in seminars and organizing accounting training activities related to the preparation of BUMDes Silatri Indah financial reports. The results of community service activities are accounting understanding managers. In seminars and training events, BUMDes managers can record every transaction in financial reports in accordance with accounting rules. Keywords: BUMDES, Accounting Process, Financial Reports